An empirical investigation into the usefulness of productivity information and value added satement to securities analysts for stock valuation - Tan, Hwee Koon (2014)
The survey was conducted on one group of financial statement users, namely the securities analysts. The main objective of the study is to investigate the usefulness of productivity information, in particular, the value added statement (VAS) in assisting the analysts in their valuation of stocks.